Removal of metronidazole from aqueous solution using activated carbon - Belhassen, Habibi; Ghorbel-Abid, Ibtissem; Rim, Lahsini (European Journal of Chemistry, 2017)
Metronidazole antibiotic is a medication once discharged into the water after use, can react with living organisms and causing adverse effects to their lives. This kind of contaminant must be removed from wastewater and the technique adopted in this work is the liquid-solid adsorption method. The removal of metronidazole in aqueous solutions is carried out on powdered activated carbon. Different parameters such as solid/liquid ratio, temperature, pH, concentration, and contact time influencing this adsorption are examined. The Langmuir isotherm appears the most satisfactory is best suited for modeling the adsorption of metronidazole. In addition, the pH and the temperature do not seem to have any noticeable effect on the adsorption of metronidazole. The experimental results showed that metronidazole was removed at 64% for concentration of 50 mg/L for contact time of 20 min.